Factors Affecting the Achievement of Complete Basic Immunization Coverage - Anur Rohmin (Miracle Journal Get Press, 2025)
Complete basic immunization is a key preventive measure to reduce morbidity and mortality in toddlers from vaccine-preventable diseases (PD3I). However, coverage in several regions still falls short of national targets. Objective: This study aims to identify factors influencing the achievement of complete basic immunization among toddlers at Posyandu Balita RW III, Anduring Subdistrict, Padang City. Methods: A quantitative cross-sectional design was used, involving 75 toddlers aged 12–23 months selected purposively. Data were collected through structured interviews with mothers and observation of child health (KIA) books. The chi-square test was used to analyze the relationship between independent variables (maternal knowledge, education, employment, family support, and access to health services) and immunization status. Results: There were significant associations between: Maternal knowledge (p=0.002), Maternal education (p=0.015), Family support (p=0.005), Access to health services (p=0.008) and complete basic immunization. However, maternal occupation did not show a significant relationship (p=0.234). Implications: The findings highlight the need for public health programs to prioritize maternal education, family involvement, and improved access to health facilities to increase immunization coverage. Conclusion: Maternal knowledge, education, family support, and access to health services are key factors influencing immunization success. These should be considered in planning and implementing effective immunization strategies.